# How do you solve 6 - |4x - 3| = -19?

Apr 29, 2017

See the entire solution process below:

#### Explanation:

First, subtract $\textcolor{red}{6}$ from each side of the equation to isolate the absolute value term while keeping the equation balanced:

$- \textcolor{red}{6} + 6 - \left\mid 4 x - 3 \right\mid = - \textcolor{red}{6} - 19$

$0 - \left\mid 4 x - 3 \right\mid = - 25$

$- \left\mid 4 x - 3 \right\mid = - 25$

Next multiply each side of the equation by $\textcolor{red}{- 1}$ to isolate the absolute value function while keeping the equation balanced:

$\textcolor{red}{- 1} \cdot - \left\mid 4 x - 3 \right\mid = \textcolor{red}{- 1} \cdot - 25$

$\left\mid 4 x - 3 \right\mid = 25$

The absolute value function takes any negative or positive term and transforms it to its positive form. Therefore, we must solve the term within the absolute value function for both its negative and positive equivalent.

Solution 1)

$4 x - 3 = - 25$

$4 x - 3 + \textcolor{red}{3} = - 25 + \textcolor{red}{3}$

$4 x - 0 = - 22$

$4 x = - 22$

$\frac{4 x}{\textcolor{red}{4}} = - \frac{22}{\textcolor{red}{4}}$

$\frac{\textcolor{red}{\cancel{\textcolor{b l a c k}{4}}} x}{\cancel{\textcolor{red}{4}}} = - \frac{2 \times 11}{\textcolor{red}{2 \times 2}}$

$x = - \frac{\textcolor{red}{\cancel{\textcolor{b l a c k}{2}}} \times 11}{\textcolor{b l a c k}{\cancel{\textcolor{red}{2}}} \times 2}$

$x = - \frac{11}{2}$

Solution 2)

$4 x - 3 = 25$

$4 x - 3 + \textcolor{red}{3} = 25 + \textcolor{red}{3}$

$4 x - 0 = 28$

$4 x = 28$

$\frac{4 x}{\textcolor{red}{4}} = \frac{28}{\textcolor{red}{4}}$

$\frac{\textcolor{red}{\cancel{\textcolor{b l a c k}{4}}} x}{\cancel{\textcolor{red}{4}}} = 7$

$x = 7$

The solution is: $x = - \frac{11}{2}$ and $x = 7$